2020
DOI: 10.1186/s12911-020-1118-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced character-level deep convolutional neural networks for cardiovascular disease prediction

Abstract: Background Electronic medical records contain a variety of valuable medical information for patients. So, when we are able to recognize and extract risk factors for disease from EMRs of patients with cardiovascular disease (CVD), and are able to use them to predict CVD, we have the ability to automatically process clinical texts, resulting in an improved accuracy of supporting doctors for the clinical diagnosis of CVD. In the case where CVD is becoming more worldwide, predictive CVD based on EMRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Reference [ 14 ] proposed an online medical decision support system for predicting chronic kidney disease. Reference [ 15 ] proposed an enhanced feature-level deep convolutional neural network model. The researchers went from initially using a machine algorithm to integrating statistical models and mathematical models into machine learning models, which further improved the prediction effect of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [ 14 ] proposed an online medical decision support system for predicting chronic kidney disease. Reference [ 15 ] proposed an enhanced feature-level deep convolutional neural network model. The researchers went from initially using a machine algorithm to integrating statistical models and mathematical models into machine learning models, which further improved the prediction effect of the model.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the results it is shown that our proposed system effectively outperforms in terms of the evaluation performance metrics. Comparative analysis of the QoS parameters of the existing methods and the proposed system[35]…”
mentioning
confidence: 99%